Factores influyentes en el éxito o fracaso de los implantes dentales osteointegrados: una revisión sistemática - Zapata Banda, Melanie Nicole (2025)
Introduction: Edentulism, defined as the total or partial absence of teeth, affects functionality and esthetics, its main causes are dental caries and periodontal disease. There are several treatment options, with fixed prostheses on osseointegrated implants being one of the ones that provides the best results. Objective: To analyze the available scientific literature on the factors that have been identified as determinants of success or failure in osseointegrated dental implants. Materials and Methods: Qualitative, descriptive and basic approach research, which used a documentary method that gathered information from databases: PubMed, ScienceDirect and LILACS, using search strings and inclusion criteria. Results: Out of 394 scientific articles, after a process of discarding and selection only 16 articles were considered for analysis and discussion. Conclusions: It was identified that technical factors have the greatest impact on implant osseointegration and thus on implant survival, while biological factors such as infections during or after implant placement should be considered for implant failure.